Word Cloud of Online Hotel Reviews in Myanmar for Customer Satisfaction Analysis - Vimolboon Cherapanukorn (2018)
© 2017 IEEE. This co-research project between Chiang Mai University and Mandalay University aims to examine the satisfied and unsatisfied of hotel customers by utilizing a word cloud approach to evaluate online reviews. An online commends of 682 hotel guests were collected from TripAdvisor.com for 6 luxury hotels in Mandalay region, Myanmar. The results revealed some common features that are identified in both satisfied and dissatisfied of customer comments; including hotel decoration, staff service skills, room amenities and traditional cuisines. Instead, the findings illustrated that dissatisfied customers mentioned frequently on a cleanliness of rooms and a poor of the Internet signal. Therefore, this articles findings suggest some greater managerial implications pertaining to understanding of customer satisfaction level through the utilization of world cloud technique via review online platforms for hotel industry in Myanmar.